Que reste-t-il des théories sociologiques de George Mendenhall et de Norman Gottwald sur l’installation des tribus israélites au pays de Canaan ? - Daniel Bodi (Yod, 2013)
Historians, sociologists, archaeologists and Bible scholars diverge consistently in their opinion concerning the Israelite installation in Canaan. Three theories where prevailing up to the end of the 20th century: the theory of William F. Albright and the Baltimore School, the theory of the German historians Albrecht Alt and Martin Noth, as well as the sociological theory of George Mendenhall and Norman Gottwald. The present article aims to analyze the contemporary scientific value of this last one.